2010
DOI: 10.1097/cej.0b013e3283354847
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma risk factors, perceived threat and intentional tanning: an international online survey

Abstract: Background Cutaneous melanoma continues to increase in incidence in many countries, and intentional tanning is a risk factor for melanoma. The aim of this study was to understand how melanoma risk factors, perceived threat, and preferences for a suntan relate to intentional tanning. Methods Self-report data were collected on behalf of GenoMEL (www.genomel.org) from members of the general population using an online survey. A total of 8,178 individuals successfully completed at least 80% of the survey, with 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
2
34
3
Order By: Relevance
“…A detailed description of the demographic characteristics of the study sample has been reported previously. 9 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the demographic characteristics of the study sample has been reported previously. 9 …”
Section: Resultsmentioning
confidence: 99%
“…9,10 In brief, recruitment took place between January 2007 and September 2008 using a web-based survey designed specifically for the study. Recruiting centers were located in 12 countries (Australia, Germany, Israel, Italy, Latvia, the Netherlands, Poland, Slovenia, Spain, Sweden, the UK and the USA) participating in the melanoma genetics consortium, GenoMEL.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of melanoma is higher in countries close to the Equator, but many cases also occur in Europe. The highest numbers of cases are reported in Switzerland, the Netherlands, Denmark, Norway, and Sweden (1)(2)(3)(4). The prevalence of melanoma in the hispanic population of the USA is about six times lower than in the Caucasian population (4,5).…”
Section: Introductionmentioning
confidence: 98%
“…Economic prosperity in Sweden has rapidly improved since the 50ies, enabling spare time for domestic sun tanning, frequent sun travels abroad and sun bed use. This is likely to have contributed to the steadily rising melanoma rates and a multicenter on-line survey 2010 has established swedes to be among the most sun seeking populations in the world [4,5].…”
Section: Introductionmentioning
confidence: 98%